Service-Oriented Computing - ICSOC Workshops 2012 ICSOC 2012, International Workshops ASC, DISA, PAASC, SCEB, SeMaPS, and WESOA, and Satellite Events, Shanghai, China, November 12-15, 2012, Revised Selected Papers - Ghose, Aditya; Zhu, Huibiao; Yu, Qi.; Delis, Alex.; Sheng, Quan Z.; Perrin, Olivier; Wang, Jianmin; Wang, Yan.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the thoroughly refereed proceedings of the 2012 ICSOC Workshops consisting of 6 scientific satellite events, organized in 3 main tracks including workshop track (ASC, DISA. PAASC, SCEB, SeMaPS and WESOA 2012), PhD symposium track, demonstration track; held in conjunction with the 10th International Conference on Service-Oriented Computing (ICSOC), in Shanghai, China, November 2012. The 53 revised papers presents a wide range of topics that fall into the general area of service computing such as business process management, distributed systems, computer networks, wireless and mobile computing, grid computing, networking, service science, management science, and software engineering.
Workshop Track -- ASC 2012 -- The 1st International Workshop on Analytics Services on the Cloud (ASC 2012) -- A Performance Evaluation of Public Cloud Using TPC-C -- An Efficient Data Maintenance Strategy for Data Service Mashup Based on Materialized View Selection -- Homomorphic-Encryption-Based Separation Approach for Outsourced Data Management -- Protecting Software as a Service in the Clouds by Validation -- Identifying Fake Feedback for Effective Trust Management in Cloud Environments -- Sonata: A Workflow Model for Interactive Mobile Cloud Applications -- Kachako: A Hybrid-Cloud Unstructured Information Platform for Full Automation of Service Composition, Scalable Deployment and Evaluation -- DISA 2012.-2012 International Workshop on Data Intensive Services Based Application (DISA2012) -- An End-User Oriented Approach for Business Process Personalization from Multiple Sources -- A Combination Approach to QoS Prediction of Web Services -- Effective and Efficient Web Reviews Extraction Based on Hadoop -- Intelligent Information Management of Tourist Attractions Based on Semantic Sensor Web - An Optimal Approach to the QoS-Based WSMO Web Service Composition Using Genetic Algorithm -- PAASC 2012 -- Introduction to the Second International Workshop on Performance Assessment and Auditing in Service Computing (PAASC 2012) -- Towards the Definition of a Framework Supporting High Level Reliability of Services -- A Service-Oriented Approach to Assess the Value of Digital Preservation -- Specification and Deployment of Distributed Monitoring and Adaptation Infrastructures -- Introducing the Vienna Platform for Elastic Processes -- SCEB 2012 -- TrustVis: A Trust Visualisation Service for Online Communities -- Crowd-Sourcing Service Designs: Overview and Research Challenges -- Towards an Architectural Framework for Service-Oriented Enterprises -- Monitoring Business Process Interaction -- Interactive Product Browsing and Configuration using Remote Augmented Reality Sales Services -- SeMaps -- The 1st International Workshop on Self-managing Pervasive Service Systems (SeMaPS 2012) -- A Reformative System Architecture of Cloud Service Based on IEEE 1851 -- Towards RESTful Communications in Self-managing Pervasive Systems -- A Research Roadmap for Context-Awareness-Based Self-managed Systems -- A 3D Model Based Action Recorder Using Computer Vision -- Protecting Sensitive Attributes in Attribute Based Access Control -- A Hybrid Indoor Positioning Approach for Supermarkets -- WESOA 2012 -- Introduction to the 8th International Workshop on Engineering Service-Oriented Applications (WESOA12) -- Towards Automated and Correct Composition of Timed Services -- Resolving Violations in Inter-process Relationships in Business Process Ecosystems -- An Aspect-Oriented Approach to Enforce Security Properties in Business Processes -- Evaluation of Quality of Design for Document-Centric Software Services -- Resource Management for Pervasive Systems -- Service Oriented Requirements Engineering: Practitioner’s Perspective -- Phd Symposium Track -- Phd Symposium Track: Message from Chairs -- Data Consistency Enforcement on Business Process Transactions -- An Auction-Based Approach for Composite Web Service Selection -- Data-Centric Probabilistic Process: A PhD. Symposium Paper for ICSOC -- Detection of SOA Antipatterns -- Requirements-Driven Software Service Evolution -- Detecting Runtime Business Process Compliance with Artifact Lifecycles -- Demo Track -- Introduction to the Demo Track -- A Dynamic SCA-Based System for Smart Homes and Offices -- Realizing Elastic Processes with ViePEP -- A Social Network Based Collaborative Video Story Composition Platform -- BPMashup: Dynamic Execution of RESTful Processes -- Soda: A Tool Support for the Detection of SOA Antipatterns -- Method and System for In-Place Modeling of Business Process Extensions as First-Class Entities -- Supporting Business and IT through Updatable Process Views: The pro View Demonstrator.
Keywords: Software engineering; Application software; Information technology; Business—Data processing; Management information systems; Computer science; Optical data processing; Software Engineering; Information Systems Applications (incl. Internet).; IT in Business; Computer Appl. in Administrative Data Processing; Management of Computing and Information Systems; Computer Imaging, Vision, Pattern Recognition and Graphics